Bi-chromaticity and tunability of random lasing in mesoporous silica SBA16 doped with rhodamine B - Melo, Leandro A. (2022)
The random laser emission from ordered mesoporous silica SBA16 doped with rhodamine B (RB) organic dye was investigated. Powdered SBA16 with 16 nm average pore diameter have been synthesized and doped with five different concentrations of the organic dye. Typical incoherent feedback random laser behavior was observed. The bi-chromatic emission was characterized for the sample with the highest dye concentration. Tunable random laser emissions from 578 to 618 nm were obtained depending on the excitation laser spot diameter and the rhodamine-B load. The results indicate that mesoporous RB-doped SBA16 is a promising material for the development of solid-state random lasers.